Presentation - Aguirre Chávez, Felipe (2021)
A new volume updates our commitment to continue calling teachers and students to intellectual work, as a priority activity that underpins the reason for being of the university institution, whose purpose is to allow research, creation, cultural process and practice teachers are integrated and empowered in an effective way. For this reason, EDUCA-UMCH intends to establish a space for the achievement of these goals and their timely dissemination.